Ideological constructions surrounding clinical psychology in a context of psychiatric (counter)reform - Sancho Quirós, Valeria (2024)
Introduction: Costa Rica started a reorganization of psychiatric hospitals in 1990. This paper is interested in the implications of this process on psychology’s scope of action. Objective: Reflecting on ideological constructions of specialists in clinical psychology, pertaining to their professional role. Method and technique: Ideology is addressed in its sociological scope, as referred to a group’s shared self definition which allows it to coordinate practices in relation to other mental health professionals and ensured persons. Semi-structured interviews with five psychology specialists, and the analysis of primary documental sources. Results: Changes and tensions in the ideological constructions surrounding the role of Specialist in Clinical Psychology are described. The relation of sponsorship with Psychiatry, and efforts to differentiate from this discipline within the framework of projects centered on functionality and rehabilitation are highlighted. Rivalry and alliances between mental health professionals are also put into focus. Conclusions: In the context of reform, Specialists in Clinical Psychology seem to be torn between the enclosure of their field of work, interdisciplinary projects, and claims of protagonism. The promotion of a model based on human rights has gone hand in hand with the expansion of the professional scope of psychology, but a part of the psychological guild has recently supported a possible psychiatric counterreform, in the name of negotiation and consensus building.